Cell signaling reactions single-molecular kinetic analysis - Sako, Yasushi; Ueda, Masahiro (Springer eBooks., 2011)
This book encompasses the exciting developments and challenges in the fast-moving and rapidly expanding research field of single-molecule kinetic analysis of cell signaling that promises to be one of the most significant and exciting areas of biological research for the foreseeable future. Cell signaling is carried out by complicated reaction networks of macromolecules, and single-molecule analyses has already demonstrated its power to unravel complex reaction dynamics in purified systems. To date, most of the published research in the field of single-molecule processes in cells, focus on the dynamic properties (translational movements of the centre of mass) of biological molecules. However, we hope that this book presents as many kinetic analyses of cell signaling as possible. Although single-molecule kinetic analysis of cellular systems is a relatively young field when compared with the analysis of single-molecule movements in cells, this type of analysis is highly important because it directly relates to the molecular functions that control cellular behavior and in the future, single-molecule kinetic analysis will be largely directed towards cellular systems. Thus, we hope that this book will be of interest to all those working in the fields of molecular and cell biology, as well as biophysics and biochemistry.